Popliteal Vein Aneurysm as Rare Cause of Recurrent Pulmonary Embolism - Sylvain Eminian; Jochen M. Grimm; Jean-Marc Corpataux; Salah Dine Qanadli (The Arab Journal of Interventional Radiology, 2017)
We present a case of popliteal venous aneurysm causing recurrent pulmonary embolism successfully treated by surgical resection.